The study of factors affecting purchase intention of halal non-consumables cooking utensils products - Bailey, Bernard; Aprilianty, Fitri (Journal of Business and Management, 2020)
Abstract. The publication of Undang-Undang No. 33 Tahun 2014 tentang Jaminan Produk Halal or a regulation about halal product guarantee stated that all of utensil products including cooking utensils need to be halal certified. But eventually the execution of the rules is still not yet reached the stages where utensil products must to be halal certified. This cause confusion, because the one that must be halal certified is cosmetic and consumables items rather than utensil products. However, nowadays in Indonesia there is already established halal brand in non-consumables cooking utensils. This research intends to finds and explore mapping of MUI certification system for non-consumables goods inIndonesia, test factors (brand images, halal awareness, halal certification, religiosity, of attitude, subjective norm, perceived behaviour control) that influence customers to buy halal cooking utensils (non-consumables) product, and test the necessity of halal branding on cooking utensils. In this research the data collected through interview and online survey towards Muslim women. Then the data analyzed by open coding and PLS-SEM to analyse the relationship between variables. The results of this research indicates that attitudes have no significant effect towards purchase intention, with perceived behavioral control as the most significant factors which affect purchase intention. Thefinding of this research expected to provide cooking pan marketer to decide whether halal branding strategy is suitable or not for their company, to avoid ineffective resources allocation for marketing.Keywords: Cooking Utensil, Halal Branding, MUI, Purchase Intention, SEM-PLS